Thresholds for surfactant use in preterm neonates: a network meta-analysis - Branagan, Aoife; Yu, Ivan; Gurusamy, Kurinchi; Miletin, Jan (Archives of disease in childhood. Fetal and neonatal edition, 2023)
OBJECTIVE: To perform a network meta-analysis of randomised controlled trials of different surfactant treatment strategies for respiratory distress syndrome (RDS) to assess if a certain fraction of inspired oxygen (FiO2) is optimal for selective surfactant therapy. DESIGN: Systematic review and network meta-analysis using Bayesian analysis of randomised trials of prophylactic versus selective surfactant for RDS. SETTING: Cochrane Central Register of Controlled Trials, MEDLINE, Embase and Science Citation Index Expanded. PATIENTS: Randomised trials including infants under 32 weeks of gestational age. INTERVENTIONS: Intratracheal surfactant, irrespective of type or dose. MAIN OUTCOME MEASURES: Our primary outcome was neonatal mortality, compared between groups treated with selective surfactant therapy at different thresholds of FiO2. Secondary outcomes included respiratory morbidity and major complications of prematurity. RESULTS: Of 4643 identified references, 14 studies involving 5298 participants were included. We found no statistically significant differences between 30%, 40% and 50% FiO2 thresholds. A sensitivity analysis of infants treated in the era of high antenatal steroid use and nasal continuous positive airway pressure as initial mode of respiratory support showed no difference in mortality, RDS or intraventricular haemorrhage alone but suggested an increase in the combined outcome of major morbidities in the 60% threshold. CONCLUSION: Our results do not show a clear benefit of surfactant treatment at any threshold of FiO2. The 60% threshold was suggestive of increased morbidity. There was no advantage seen with prophylactic treatment. Randomised trials of different thresholds for surfactant delivery are urgently needed to guide clinicians and provide robust evidence. PROSPERO REGISTRATION NUMBER: CRD42020166620.
Keywords: Pulmonary Surfactants; těhotenství; Bayes Theorem; Surface-Active Agents; Respiratory Distress Syndrome, Newborn; Network Meta-Analysis as Topic; povrchově aktivní látky; plicní surfaktanty; Bayesova věta; Infant, Newborn; ženské pohlaví; novorozenec; síťová metaanalýza; Humans; syndrom respirační tísně novorozenců; Pregnancy; Infant, Premature; Female; novorozenec nedonošený; lidé